Entrepreneurial Learning and Innovation: Preliminary Findings from a Validation Study of Assessment Instrument - Stacey Robbins (Adult Education Research Conference, 2014)
While interest in entrepreneurship and entrepreneurship education grows, how to develop and support entrepreneurs remains poorly understood (Heinonen & Akola, 2007). This paper explores core capacities for entrepreneurial learning and innovation through a literature review and initial validation of measures tapping behaviors and attitudes via a survey instrument.